What Color is Your C.F.R.? - Dyszlewski, Nicole; Gotauco, Elizabeth; M. Ortiz, Raquel; Open Textbook Library (Open Textbook Library, 2016)
What Color is Your C.F.R.? is a problem-based law workbook with a colorful twist. Conceived and written by law librarians, it uses easy to understand plain language and is a light-hearted but helpful supplement to instruction on basic legal research. The book takes a non-traditional approach to legal research and uses short legal research exercises and coloring.
This coloring book is going to take a non-traditional approach to legal research. We are going to feature short legal research exercises and coloring. We hope you can start to see that legal research, like coloring, can be fun! --
In English.
Description based on online resource
Keywords: Law -- Textbooks -- United States